KINERJA PEGAWAI PENGAWAS KETENAGAKERJAAN DI DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SULAWESI UTARA - Donald Adolf Kolly; Stefanus ., Sampe; Johny P. Lengkong (AGRI-SOSIOEKONOMI, 2021)
This study aims to analyze and describe the performance of supervisory employees at the Department of Manpower and Transmigration of North Sulawesi Province. The method used in this research is descriptive qualitative method with data collected in the form of words and pictures. The focus of this research is based on the factors that affect the performance of employees which consist of quality of work, quantity of work, use of time and cooperation. Data collection techniques used are interviews, observation, and documentation. The data collected was analyzed through several stages, namely data reduction, display and data verification. The results showed that the performance of the supervisory staff of the Disnakertrans of North Sulawesi Province was very good even though there were several obstacles in carrying out their respective tasks.